Diseño y construcción de un modelo híbrido de refrigeración solar eléctrico por absorción, utilizando tecnología local. - Flores Alvarado, Walter Efraín (2011)
In this work there was evaluated a prototype of refrigerator designed and to construct for absorption hybrid, electrical efficient lot of cycle Ammonia - water with a cylindrical parabolic collector. For the development of the work I initiate with a bibliographical summary on solar refrigeration for absorption and systems of solar concentration. Whose energetic source is principally the solar power. With the experimentation there were obtained the such parameters of functioning of the refrigerator as: power demanded by the equipment, the range of temperatures of work of all the components of the cycle. There appear the results obtained with two experiments of the refrigerator produced with electricity and with solar power. The principal reasons of mistake appear and they propose the recommendations to improve the process.